2012
DOI: 10.1080/10826068.2012.654571
|View full text |Cite
|
Sign up to set email alerts
|

IMMOBILIZATION OF CARBONIC ANHYDRASE ENZYME PURIFIED FROMBacillus subtilisVSG-4 AND ITS APPLICATION AS CO2SEQUESTERER

Abstract: The purification, immobilization, and characterization of carbonic anhydrase (CA) secreted by Bacillus subtilis VSG-4 isolated from tropical soil have been investigated in this work. Carbonic anhydrase was purified using ammonium sulfate precipitation, Sephadex-G-75 column chromatography, and DEAE-cellulose chromatography, achieving a 24.6-fold purification. The apparent molecular mass of purified CA obtained by SDS-PAGE was found to be 37 kD. The purified CA was entrapped within a chitosan-alginate polyelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Wu, Liu, Zhou, Wang, Xia and Liu () isolated three active secondary metabolites from Alcaligenes faecalis FY‐3 that induce immune‐related gene expression in C. idellus kidney cells. Oviya, Giri, Sukumaran and Natarajan () and Giri, Sen, Jun, Sukumaran and Park () demonstrated that B. subtilis VSG4, isolated from tropical soil, produces carbonic anhydrase, and the secondary metabolite (a biosurfactant) isolated from this strain (200 μg mL ‒1 ) positively influences immune responses, enhances disease resistance and stimulates immune‐related gene expression in L. rohita . The results of Giri et al .…”
Section: Microorganismsmentioning
confidence: 98%
“…Wu, Liu, Zhou, Wang, Xia and Liu () isolated three active secondary metabolites from Alcaligenes faecalis FY‐3 that induce immune‐related gene expression in C. idellus kidney cells. Oviya, Giri, Sukumaran and Natarajan () and Giri, Sen, Jun, Sukumaran and Park () demonstrated that B. subtilis VSG4, isolated from tropical soil, produces carbonic anhydrase, and the secondary metabolite (a biosurfactant) isolated from this strain (200 μg mL ‒1 ) positively influences immune responses, enhances disease resistance and stimulates immune‐related gene expression in L. rohita . The results of Giri et al .…”
Section: Microorganismsmentioning
confidence: 98%
“…The immobilized forms are efficient and can be used for industrial purposes. The CA isolated from B. subtilis VSG4 convert CO 2 into CaCO 3 in the immobilized form (Oviya et al, 2012). Bacillus sp.…”
Section: Improvement Of Soil Qualitymentioning
confidence: 99%
“…We previously showed that Bacillus subtilis VSG4, isolated from tropical soil (Oviya et al, 2012), produces biosurfactant that stimulates immune responses and cytokine gene expression in rohu ( Labeo rohita ), in addition to enhancing resistance to A. hydrophila infection in carp (Giri et al, 2016c). In the present study, a biosurfactant-producing strain, Bacillus licheniformis , was isolated from food waste.…”
Section: Introductionmentioning
confidence: 99%